Distributed mobility in dynamic environments - Carvalho, Jonathan Gabriel Oliveira (2014)
Conventional networks have implemented a specific hierarchical structure, which in many cases deals with centralized mobility anchoring models to ensure IP session continuity. In this context, mobility management demands the existence of a centralized and static anchor point to allow reachability to mobile nodes connected to distinct networks. However, such centralized element is a single point of failures, introducing longer delays and higher management signalling. It may be more vulnerable to attacks, causing problems in the system. For this reason, mobility management addressed to centralized models is a satisfactory and non-optimal solution when mobile networks become less hierarchical. In order to improve mobility management to meet the requirements in mobile network evolution, there have been proposed solutions to distribute the anchor points closer to the end-user. This way, distributed and dynamic mobility anchoring improves scalability and availability, avoiding single points of failure and bottlenecks, as well as enabling transparent mobility support. In this framework, it is idealized and implemented a set of Vehicular scenarios using two different types of mobility management models, one centralized and another distributed. The results shows that the distributed mobility management protocol provides better results in terms of data loss, average data delay, data cost and signaling cost, when compared with the centralized mobility management protocol. The rapid growth of mobile nodes has lead to the increase of mobile data traffic consumption, and they are currently equipped with multiple network interfaces, which in many cases use different access technologies simultaneously. Therefore, session continuity of a certain user's services should be guaranteed independently of the access network technology. Consequently, there is a fundamental change in the network architectures, which is adopting flatten model to cope with users' behaviour and the evolution of the mobile data traffic consumption. Thus, it is specified a distributed mobility management scheme with multihoming support to provide continuity to active sessions when mobile nodes roam between networks/interfaces. This mobility mechanism is evaluated and tested in a real environment, demonstrating the capability to provide uninterrupted sessions for multihomed scenarios, such as the addition/removal of a link, likewise the capability to improve user experience.